Pendampingan UMKM Melalui Branding Logo Sebagai Identitas Produk Limunite di Kelurahan Sukorejo Kota Blitar - Faradiah Khasny; Arief Bachtiar; Kiki Asmara (Jurnal Masyarakat Mengabdi Nusantara, 2023)
MSMEs or Micro, Small and Medium Enterprises are one of the factors for the Indonesian economy to survive and develop until now. By increasing the use and shopping of domestic products, it can help increase the growth of MSMEs, as well as the welfare of the community. In building MSMEs, branding needs to be done to build and elevate the identity of a brand, including trade names, logos, characters, and consumer responses. In branding a product can be seen directly by consumers, namely through logos and packaging that has special characteristics, so that consumers can recognize these products. Packaging becomes a direct view by consumers to the product, so that attractive packaging can attract attention. On the packaging can be listed such as trade names, logos, nutritional values, and various important information in the product so that it can build trust.